Intersection rotational invariance regression based plant disease detection - J. Senthil; N. K. Karthikeyan; R. Senthilkumar (Plant Molecular Biology, 2026)

A Review on Potato Dormancy Prediction and Sprouting Detection Methods: Advancements in Analytical Technologies for Postharvest Physiology - T. Senthilkumar; S. Ramalingam; R. K. Goraya; U. C. Lohani; C. B. Singh (Potato Research, 2026)

Flexural restoration of deficient RC beams using unidirectional basalt textile-reinforced polymer through optimized surface preparation - T. Vijay; R. Senthilkumar; Keerthan Poologanathan (Innovative Infrastructure Solutions, 2026)

Development of axial–moment interaction curves for flat and square-profiled cold-formed steel–concrete composite shear walls using experimental and numerical investigations - Uma Chandru; R. Senthilkumar (Bulletin of Earthquake Engineering, 2026)

Green fabrication of starch/PVA/CuO nanoscaffolds using marine macroalgae extract for enhanced anti-inflammatory activity - JinJin Pei; Mathangi Vinayakar Senthilkumar; Kamel Hessini; Suresh Subramaniyam; R Sivaramakrishnan; Gopalakrishnan Velliyur Kanniappan; Selvaraj Jayaraman; Chella Perumal Palanisamy (Sustainable Chemistry and Pharmacy, 2026)

Retraction notice to “Unearthing Earth's secrets: Exploring the environmental legacy of contaminants in soil, water, and sediments” [Environ. Res. 249 (2024) 118246] - Gautham Devendrapandi; Ranjith Balu; K. Ayyappan; Ramamoorthy Ayyamperumal; Salh Alhammadi; Mahimaluru Lavanya; R. Senthilkumar; P.C. Karthika (Environmental Research, 2026)

A Walking Type Self-Propelled Single-Row Carrot Harvester-Cum-Detopper for Hilly Region - T. Senthilkumar; S. Syed Imran; G. Manikandan; R. Sanjay Krishnan (Agricultural Research, 2026)

Hierarchical SPEES nanocomposite ionomer with phosphomolybdic acid decorated Co3O4 nanofiller as PEM for microbial fuel cells: An anti-biofouling and scale-up approach - John Solomon; Akshaya Senthilkumar; Naveen Rajkumar Sivakumar; R. Devi; Sangeetha Dharmalingam (Journal of Environmental Management, 2026)

An extensive evaluation framework employing analytical, numerical, and probabilistic methods to assess irregularity in RC buildings on hill slopes during earthquakes - Babaji Patil; Ananda Mitra; L. Aditya; G. Tamizharasi; R. Senthilkumar (Soil Dynamics and Earthquake Engineering, 2026)

Mitigating pounding through drift limitations: a focus on buildings with re-entrant corner - Ananda Mitra; Shailesh Lahoti; A. Laghate; G. Tamizharasi; R. Senthilkumar (Innovative Infrastructure Solutions, 2025)

Integrated deterministic and probabilistic assessment of reinforced concrete buildings featuring transfer structures under earthquake shaking - Vikrant Parthe; L. Aditya; Ananda Mitra; G. Tamizharasi; R. Senthilkumar (Bulletin of Earthquake Engineering, 2025)

Retraction notice to “Investigation of pure and g-C3N4 loaded CdWO4 photocatalytic activity on reducing toxic pollutants” [Chemosphere 291, Part 3, March 2022, 133090] - S.P. Keerthana; R. Yuvakkumar; P. SenthilKumar; G. Ravi; S.I. Hong; Dhayalan Velauthapillai (Chemosphere, 2025)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

SG06, a Chalcone Derivative Targets PI3K/AKT1 Pathway for Neuroprotection and Cognitive Enhancement in an Alzheimer’s Disease-Like Zebrafish Model - Santhanam Sanjai Dharshan; Meghana R; Shreya Madhankumar Rao; B. Aswinanand; Karthikeyan Ramamurthy; Muthumareeswaran Muthuramamoorthy; M. Valan Arasu; Kathiravan Muthu Kumaradoss; Ajay Guru; Senthilkumar Palaniappan; Jesu Arockiaraj (Molecular Neurobiology, 2025)

Pharmacognostical and Anatomical Insights into Sargassum polycystum: A Marine Brown Algae with Pharmaceutical and Medicinal Potential - R. Vijaya Gandhi; M. Senthilkumar; Dharmalingam Kirubakaran (Thalassas: An International Journal of Marine Sciences, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Nanoplastics in heat-sensitive food packaging: A review of migration, detection, health, and environmental impacts - Senthilkumar Palanisamy; Barani Kumar Saravana Kumar; Aishwarya Vetrivel; Rahul Jacob Michael; Nivethitha Babu; Sanjay Sharan Nallamuthu; Kokila Saravanan; Shanmugam Venkatachalam; Naveen Kumar R J; Gayathri Devi Selvaraju; Rajendran K. Selvakesavan; Jintae Lee; et al. (Food Control, 2025)

Improved charge carriers separated heterojunction photocatalyst ZnO2/2D g-C3N4 for rapid and enhanced degradation of ciprofloxacin: Pathways & toxicity assay - Dhakshnamoorthi Harikaran; Aman Shukla; Ashwin Sudarshan Suresh; Ramasamy Shanmugam; Sellappan Senthilkumar; Jagannathan Madhavan; Vijayaraghavan R (Journal of Water Process Engineering, 2025)

K-means Pelican Optimization Algorithm based Search Space Reduction for Remote Sensing Image Retrieval - W. T. Chembian; G. Senthilkumar; A. Prasanth; R. Subash (Journal of the Indian Society of Remote Sensing, 2025)

Evaluating the availability and carbon footprint of agricultural waste ashes: a strategy for achieving sustainable cement production in India - Uma Chandru; A. Bahurudeen; R. Senthilkumar; T. Vijay (Innovative Infrastructure Solutions, 2024)

Recent advancements in nanotechnological approaches for pollution monitoring and environmental sustainability - J. Manjunathan; M. Revathi; H. Sowmya; S. S. Meenambiga; R. Sudha; B. Prakash; Senthilkumar Nangan; Lalitha Gnanasekaran; N. Thirumalaivasan (Clean Technologies and Environmental Policy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Coastal aquatic pollutants degradation using ZnCo2O4 nanorods - Lalitha Gnanasekaran; Gomathi Ramalingam; R. Suresh; Senthilkumar Nangan; Anna Zielińska-Jurek; Wei-Hsin Chen; Matias Soto-Moscoso (Environmental Research, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Interactive behavior of cadmium ions onto polyethylene microplastics in aquatic system - D. M. Reddy Prasad; B. S. Naveen Prasad; R. Senthilkumar; K. Saravana Kumar; S. Manickkam (International Journal of Environmental Science and Technology, 2024)

EV charging and fuel cell vehicle refuelling with distributed energy resources using hybrid approach - M. Senthilkumar; Sandeep Prabhu; U. Arun Kumar; R. Krishnakumar (Environment, Development and Sustainability, 2024)

Enhancing rainwater harvesting and groundwater recharge efficiency with multi-dimensional LSTM and clonal selection algorithm - N. Raghava Rao; Sree Pokkuluri Kiran; Tamboli Amena I; A. Senthilkumar; R. Sivakumar; M. Ashok Kumar; Sampathkumar Velusamy (Groundwater for Sustainable Development, 2024)

RETRACTED: Unearthing Earth's secrets: Exploring the environmental legacy of contaminants in soil, water, and sediments - Gautham Devendrapandi; Ranjith Balu; K. Ayyappan; Ramamoorthy Ayyamperumal; Salh Alhammadi; Mahimaluru Lavanya; R. Senthilkumar; P.C. Karthika (Environmental Research, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

BIN1 in the Pursuit of Ousting the Alzheimer’s Reign: Impact on Amyloid and Tau Neuropathology - Ishnoor Kaur; Tapan Behl; G. Sundararajan; P. Panneerselvam; A. R. Vijayakumar; G. P. Senthilkumar; T. Venkatachalam; Dharmender Jaglan; Shivam Yadav; Khalid Anwer; Neeraj Kumar Fuloria; Aayush Sehgal; et al. (Neurotoxicity Research, 2023)

Assessment of solar thermal monitoring of heat pump by using zeolite, silica gel, and alumina nanofluid - G. Antony Casmir Jayaseelan; A. Surenderpaul; T. Thandial Selvam; A. Anderson; A. Senthilkumar; Avinash Malladi; R. Venkatesh; V. N. Aneesh; R. Saravanan (Clean Technologies and Environmental Policy, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Progress and challenges in double skin steel–concrete composite walls: a review - R. Senthilkumar; Pradeesh Karunakaran; Uma Chandru (Innovative Infrastructure Solutions, 2023)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Effective batch and column remediation of zinc(II) from synthetic and electroplating effluents using biochar from brown alga - R. Senthilkumar; Krishnan Saravanakumar; D. M. Reddy Prasad; B. S. Naveen Prasad; Feroz Shaik (International Journal of Environmental Science and Technology, 2022)

Reuse of Uncontrolled Burnt Bagasse Ash from Sugar Industries with Waste Rubber Powder in Construction: A Waste to Wealth Approach for Sugar Mills - K. S. Teja; R. Senthilkumar; G. Athira; A. Bahurudeen (Sugar Tech, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Biostimulant activity of sulfated polysaccharide extract from red seaweed Halymenia dilatata on yield of Mung bean in greenhouse conditions - S. Vinoth; P. Gurusaravanan; M. Arun; M. Saradhadevi; N. Senthilkumar; P. Gowtham; S. R. Sivakumar (Journal of Applied Phycology, 2021)

Aquaporin and its effect on foliar uptake to overcome drought stress in plants - Mahendran R. Vignesh; Senthilkumar Palanisamy (Plant Physiology Reports, 2021)

Stability of micro-tidal inlets along coastlines dominated by littoral drift - R. Senthilkumar; K. Murali; V. Sundar (Journal of Coastal Conservation, 2017)

Fluoride hydrogeochemistry and its occurrence in drinking water in Morappur region of Dharmapuri District, South India - M. Panneer; R. Sivakumar; M. Senthilkumar (International Journal of Environmental Science and Technology, 2017)

Analysis of the Structural Stability Among Cyclotide Members Through Cystine Knot Fold that Underpins Its Potential Use as a Drug Scaffold - B. Senthilkumar; R. Rajasekaran (International Journal of Peptide Research and Therapeutics, 2017)

Diagnosis of Mycobacterium bovis in Captive Sloth Bears (Melursus ursinus) by Polymerase Chain reaction - M. Veeraselvam; R. Sridhar; T. M. A. Senthilkumar; P. Perumal; M. G. Jayathangaraj (Proceedings of the Zoological Society, 2015)

Effects of geological structures on groundwater flow and quality in hardrock regions of northern Tirunelveli district, southern India - M Senthilkumar; R Arumugam; D Gnanasundar; D S C Thambi; E Sampath Kumar (Journal of Earth System Science, 2015)

Are mini DNA-barcodes sufficiently informative to resolve species identities? An in silico analysis using Phyllanthus - R. SRIRAMA; B. R. GURUMURTHY; U. SENTHILKUMAR; G. RAVIKANTH; R. UMA SHAANKER; M. B. SHIVANNA (Journal of Genetics, 2014)

Risk modulation of GSTM1–GSTT1 interactions to head and neck cancer in tobacco users - K. P. Senthilkumar; R. Thirumurugan (Molecular Biology Reports, 2014)

Computational analysis of deleterious missense mutations in aspartoacylase that cause Canavan’s disease - K. Sreevishnupriya; P. Chandrasekaran; A. Senthilkumar; R. Sethumadhavan; V. Shanthi; P. Daisy; J. Nisha; K. Ramanathan; R. Rajasekaran (Science China Life Sciences, 2012)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Sedimentation and trace metal distribution in selected locations of Sundarbans mangroves and Hooghly estuary, Northeast coast of India - Kakolee Banerjee; B. Senthilkumar; R. Purvaja; R. Ramesh (Environmental Geochemistry and Health, 2012)

Stability Assessment of Injectable Castor Oil-Based Nano-sized Emulsion Containing Cationic Droplets Stabilized by Poloxamer–Chitosan Emulsifier Films - S. Tamilvanan; B. Ajith Kumar; S. R. Senthilkumar; Raj Baskar; T. Raja Sekharan (AAPS PharmSciTech, 2010)

Hybrid performance for yield and yield components in cardamom (Elettaria cardamom Maton) - D. Prasath; M. N. Venugopal; R. Senthilkumar; N. K. Leela (Euphytica, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Plant Growth–Promoting Methylobacterium Induces Defense Responses in Groundnut (Arachis hypogaea L.) Compared with Rot Pathogens - M. Madhaiyan; B. V. Suresh Reddy; R. Anandham; M. Senthilkumar; S. Poonguzhali; S. P. Sundaram; Tongmin Sa (Current Microbiology, 2006)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Delineation of potential zones for artificial recharge using gis - V Jothiprakash; G Marimuthu; R Muralidharan; N Senthilkumar (Journal of the Indian Society of Remote Sensing, 2003)

Butyltin Compounds in River Otters (Lutra canadensis) from the Northwestern United States - K. Kannan; R. A. Grove; K. Senthilkumar; C. J. Henny; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1999)